Analytical performance of a platform for point-of-care CRP testing in adults consulting for lower respiratory tract infection in primary care - Matheeussen, V; Van Hoof, V; Loens, K; Lammens, C; Vanderstraeten, A; Coenen, S; Butler, C; Little, P; Verheij, T; Goossens, H; Ieven, M (Springer, 2018)
Background C-reactive protein (CRP) is a biomarker widely used for disease severity assessment and treatment of inflammatory conditions. Point-of-care testing (POCT) devices should ideally be rapid and provide similar results to standard tests done in laboratories. Methods 2922 serum samples were obtained from adult patients presenting to primary care with symptoms of lower respiratory infection in a European diagnostic study. The analytic performance of the CRP QuikRead POCT device (Orion Diagnostica) was evaluated by comparing results with a central laboratory method (Dimension Vista, Siemens), with both tests performed in a laboratory setting. Results For a CRP cut-off concentration of ≥ 30 mg/L, the QuikRead test had a sensitivity of 92.2%, and specificity of 99.4%. The mean difference between QuikRead and the central lab test was 0.4 mg/L. The slope of the Passing-Bablok regression was 0.94 (95% CI 0.93-0.95) indicating an underestimation of CRP levels of 6% by QuikRead. Conclusions CRP estimates obtained from the QuikRead test correlate well with a central laboratory assay and the measurement displays low inter-assay variation. Therefore, the QuikRead test is a good candidate for CRP testing in primary care.